Level of Knowledge and Attitude of Dried Fish Traders Toward Their Interest in Utilizing Digital Markets Along the Coast of Malabero Village, Bengkulu City - Hayyu Ghani Hamid Hamid; Herri Fariadi; Rika Dwi Yulihartika (Perkumpulan Dosen Muda (PDM) Bengkulu, 2026)
Purpose: This study aims to examine the level of knowledge and attitudes of dried fish traders and analyse their influence on the interest in utilising digital markets along the coastal area of Malabero Village, Bengkulu City. Methodology: A quantitative descriptive approach was employed using a census method, involving all 13 dried fish traders as respondents. Data were collected through observation, interviews, and questionnaires using a four-point Likert scale and analysed using multiple linear regression with SPSS. Results: The results indicate that traders’ interest in utilising digital markets is categorised as high. Knowledge (t = 5.411; p < 0.05) and attitude (t = 3.538; p < 0.05) have positive and significant effects on interest. Simultaneously, both variables significantly influence interest (F = 34.997; p < 0.05). The coefficient of determination (R² = 0.875) shows that 87.5% of the variation in interest is explained by knowledge and attitude. Findings: Knowledge is identified as the most dominant factor influencing traders’ interest in utilising digital markets. Novelty: This study highlights digital literacy among small-scale coastal traders, a group that remains underexplored in digital market adoption studies. Originality: The research provides empirical evidence from a limited coastal trading community using a census approach. Conclusion: Knowledge and attitude significantly influence traders’ interest; however, the small sample size (n = 13) limits generalisation. Enhancing digital literacy through training and support is essential. Type of Paper: Research Article